Fluid inclusions of quartz-carbonate veins in the Canadian Rocky Mountains - LaRiviere, Sarah (My University, 2015)
Vein systems in crustal rocks record a variety of processes, including fluid migration and extensive mass transfer, and they preserve information about the composition, temperature, and pressure conditions that mitigate rock-fluid interaction during vein formation. This study will attempt to characterize the formational sequence and origin of fluid inclusions observed in several samples extracted from a quartz-carbonate vein system in the Canadian Rocky Mountains, and explore the role of fluid-rock interaction in the formation of these veins. Preliminary observations of thin sections taken from vein samples are detailed conjointly with petrographic images and a brief review of the formation and significance of fluid inclusions in rock-hosted vein systems.
Presented on May 1, 2015 at the Undergraduate Research in Science Conference of Alberta (URSCA) held at MacEwan University in Edmonton, Alberta.
Keywords: fluid inclusions; quartz-carbonate veins; Canadian Rocky Mountains